What every engineer should know about the internet of things - DeFranco, Joanna F.; Kassab, Mohamad (Boca Raton, FL : CRC Press, 2022)
"This practical text provides an introduction to Internet of Things (IoT) that can be understood by every engineering discipline and discusses detailed applications of IoT"--
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; COMPUTERS / Computer Engineering; TECHNOLOGY / General